2011
DOI: 10.1111/j.1476-5381.2011.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium integrity is crucial for the relaxant activity of brain natriuretic peptide in human isolated bronchi

Abstract: BACKGROUND AND PURPOSEBrain natriuretic peptide (BNP) plays an important role in several biological functions, including bronchial relaxation. Here, we have investigated the role of BNP and its cognate receptors in human bronchial tone. EXPERIMENTAL APPROACHEffects of BNP on responses to carbachol and histamine were evaluated in non-sensitized, passively sensitized, epitheliumintact or denuded isolated bronchi and in the presence of methoctramine, N w -nitro-L-arginine methyl ester (L-NAME) and aminoguanidine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 64 publications
1
55
0
Order By: Relevance
“…This finding suggests that BNP may interact with the muscarinic receptor signalling, mainly with the M 2 receptor subtype, regulating the airway smooth muscle function [6]. BNP-dependent relaxant activity is also coupled to the increase of iNOS transcript levels in the isolated bronchi but not in bronchial epithelial cells, and the inhibition NO synthesis by aminoguanidine abolished bronchial relaxant effects [4].…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…This finding suggests that BNP may interact with the muscarinic receptor signalling, mainly with the M 2 receptor subtype, regulating the airway smooth muscle function [6]. BNP-dependent relaxant activity is also coupled to the increase of iNOS transcript levels in the isolated bronchi but not in bronchial epithelial cells, and the inhibition NO synthesis by aminoguanidine abolished bronchial relaxant effects [4].…”
mentioning
confidence: 82%
“…The BNP-related relaxation of human isolated bronchi, particularly in passively sensitized tissues, suggests that many local factors might regulate the biological activity of BNP [3]. In effect, epithelial integrity is needed for BNP-related post-transductional mechanisms regulating human bronchial contractility in response to both cholinergic and histaminergic stimulation [4]. In humans, acetylcholine has been found in epithelial cells and several studies confirm the pathobiological role of the non-neuronal cholinergic system [5,6].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…BNP mechanism of action also involved ASM relaxation (Matera et al 2009, Edelson et al 2013). However, the relaxing effect is mediated indirectly through the epithelium (Matera et al 2011).…”
Section: Heartmentioning
confidence: 99%
“…Moreover, in humans, exogenous ANP reverses airway hyper-responsiveness when given intravenously or by inhalation in high doses, although it seems to be less effective when administered by inhalation (Angus et al, 1993(Angus et al, , 1994a, and has also been shown to modify bronchial responsiveness to inhaled histamine (Angus et al, 1995) and nebulized water (Mcalpine et al, 1992). We have documented that BNP, which is able to induce a time-and concentration-dependent increase of cGMP levels in human ASM cells (Hamad et al, 2003), induces a weak but intriguing relaxant effect on human ASM (Matera et al,476 CAZZOLA ET AL. 2009) through the activation of the natriuretic peptide receptor-A (Matera et al, 2011a). The incubation of human ASM with BNP can elicit a significant reduction of cholinergic and histaminergic responses (Matera et al, 2011a).…”
Section: E Brain Natriuretic Peptide and Analogsmentioning
confidence: 99%